2020
DOI: 10.5334/paah.57
|View full text |Cite
|
Sign up to set email alerts
|

A Current Review of Foot Disorder and Plantar Pressure Alternation in the Elderly

Abstract: Fall is a very common injury, especially in older adults with foot deformities and other foot disorders. Even a small fall may cause fatal damage to this cohort. The purpose of this study was to conduct a review elucidating plantar pressure pattern under different foot deformities in the elderly. English-language search of the electronic databases in PubMed, ScienceDirect, Google Scholar, and Web of Science was conducted from 2000 to May 2020. Fifteen studies were found after literature searching and screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…All indices indicated an increased incidence of the hollow feet, both right and left ones. Numerous studies highlight that a change in foot loading paradigm is associated with an alteration in the structure of the longitudinal foot arch [ 19 , 26 , 27 ]. As evidenced by our own research, an increased loading in the hollow feet, as assessed by KY and SI CSI indices on the forefoot and hindfoot area, in zones B, E, F, is statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…All indices indicated an increased incidence of the hollow feet, both right and left ones. Numerous studies highlight that a change in foot loading paradigm is associated with an alteration in the structure of the longitudinal foot arch [ 19 , 26 , 27 ]. As evidenced by our own research, an increased loading in the hollow feet, as assessed by KY and SI CSI indices on the forefoot and hindfoot area, in zones B, E, F, is statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional linear analyses of plantar pressure such as peak plantar pressure and regional distribution ratios (forefoot versus rear foo) have been proposed in these low-cost systems. e bidimensional multiscale entropy method used in this study can be integrated into those systems for improving the detection of pathological gait by characterizing nonlinear features of plantar pressure [47].…”
Section: Discussionmentioning
confidence: 99%
“…Weight bearing can be transferred from the forefoot to the longitudinal and metatarsal arches by the metatarsal pad; however, no changes in pressure and impact forces were found in the medial forefoot region reported by Yung and Wei [ 22 ]. Furthermore, medial forefoot pads with different foam hardness and thickness were utilized; and the results showed that the thick soft pad can effectively reduce larger pressure and impact force caused by HH in the medial forefoot when compared to other types [ 7 , 43 ].…”
Section: Discussionmentioning
confidence: 99%